Hegemony of Gender Ideology Through Hyperbody of Indonesian Artificial Intelligence - Agustin, Sari Monik (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Some time ago, Indonesia was amazed by the presence of a female celebrity named "Lentari van Lorainne" who is familiarly called Riri. Riri's figure is the center of attention because she is Indonesia's first virtual celebrity created based on Artificial Intelligence (AI). The media depiction of Riri's figure is very identical to the depiction of the feminine gender promoted by patriarchy. This article will use Gramsci's thinking about Hegemony, and is equipped with the concepts of hyperbody, gender ideology, gender stereotypes and Artificial Intelligence. The paradigm used is critical with a text analysis method from the most posts on Lentari van Lorainne's account, @lentaripagi. The results of the research show that the figure of Riri also perpetuates gender stereotypes of the female body by presenting Riri as a young woman with beautiful associations that make people stunned, has an ideal body and a beautiful Indonesian-Dutch face, likes sports and travelling and is charming. This perpetuation occurs through posts and comments on Riri's Instagram account. This perpetuation was carried out by the traditional intellectuals behind the creation of the character Riri as a hyperentity. There is no counter to the hegemony of gender ideology found in this paper.